The Effect of Dry Mix Sodium Hydroxide onto Workability and Compressive Strength of Geopolymer Paste - Mohd Ali, Ahmad Zurisman; Zulkiflee, Normarliana; Jalaluddin, Nur Amelia (International Journal of Integrated Engineering, 2020)
The production of ordinary Portland cement (OPC) consumes considerable amount of natural resources, energy and at the same time contribute in high emission of CO2 to the atmosphere. A new material replacing cement as binder called geopolymer is alkali-activated concrete which are made from fly ash, sodium silicate and sodium hydroxide (NaOH). It is proven that geopolymer has excellent reaction resistance to both conditions which is in acid and salt environment hence the strength escalated as the curing time and temperature increased. The NaOH are available in pellet form and needs to be dissolved in water before mixing with sodium silicate to form alkaline solution. The alkaline solution mixed with fly ash producing alternative binder to OPC binder in concrete named geopolymer paste. Geopolymer paste acts as binder in concrete and known as geopolymer concrete. The time needed for the NaOH was 24 hours until it fully dissolved in water and cooled to room temperature. This study aims to eliminate this process by using NaOH in solid form as part of dry mixtures together with fly ash before sodium silicate liquid and water poured into the mixture. The amount of NaOH solids were based on 10M concentration. The workability test is in accordance to ASTM C230. Fifty cubic mm of the geopolymer paste were prepared with fly ash to alkaline solution ratio of 1: 0.5 and the curing regime of 80â„ƒ for 24 hours with 100% humidity were implemented. From laboratory test, the workability of dry method geopolymer paste decreased. The compressive strength of the dry mix of NaOH showed 55% strength reduction compared with conventional geopolymer paste casting method compared to the wet mix method while the workability has dropped 58.4% compared to wet mix.